Analisis Sistem Terhadap Penilaian Kinerja Karyawan pada PT. Flypower - Bunevasius Pekelmus; Agus Budiyantara (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
This research aims to analyze the effectiveness of the employee performance appraisal system at PT. Flypower, a company engaged in the production of badminton equipment since 2002 employee performance appraisal is an important component in human resource management, which involves evaluating employee contributions to achieving company goals through assessing achievements identifying strengths and weaknesses and providing feedback. This research uses a descriptive qualitative approach method. This method is used to describe phenomena related to human resource management and to understand the meaning contained in employee experiences related to the assessment system implemented data was collected through in-depth interviews participatory observation, and analysis of relevant documents, as many as 20 employees were involved as respondents to get a comprehensive perspective on the existing assessment system. The research results show that the performance appraisal system at PT. Flypower has experienced a development from a simple assessment method to a more structured system based on document analysis, in line with the implementation of the ISO 9001 standard. Transparency and regular feedback contribute positively to employee motivation. However, there are several weaknesses, such as a lack of clarity in the assessment criteria which can hinder employee understanding. This research recommends improvements in the communication of assessment criteria and the provision of understanding resources to support achievement of performance targets.